3x+7/x-2-x-4/3x-6

Simple and best practice solution for 3x+7/x-2-x-4/3x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7/x-2-x-4/3x-6 equation:


D( x )

x = 0

x = 0

x = 0

x in (-oo:0) U (0:+oo)

3*x-x-((4/3)*x)+7/x-6-2 = 0

3*x-x+(-4/3)*x+7/x-6-2 = 0

2/3*x^1+7*x^-1-8*x^0 = 0

(2/3*x^2-8*x^1+7*x^0)/(x^1) = 0 // * x^2

x^1*(2/3*x^2-8*x^1+7*x^0) = 0

x^1

(2/3)*x^2-8*x+7 = 0

(2/3)*x^2-8*x+7 = 0

DELTA = (-8)^2-(4*7*(2/3))

DELTA = 136/3

DELTA > 0

x = ((136/3)^(1/2)+8)/(2*(2/3)) or x = (8-(136/3)^(1/2))/(2*(2/3))

x = 3/4*((136/3)^(1/2)+8) or x = 3/4*(8-(136/3)^(1/2))

x in { 3/4*(8-(136/3)^(1/2)), 3/4*((136/3)^(1/2)+8)}

x in { 3/4*(8-(136/3)^(1/2)), 3/4*((136/3)^(1/2)+8) }

See similar equations:

| 8(a+2)=88 | | 11=6c-7 | | 4x+39=13 | | 6(x/2-y/3)=6(5/6) | | 4y-10+y+60=5y+50-3y | | 4y-7=28 | | x/5-y/4=15/10 | | 5x-11y=44 | | 2ln(x+6)=4 | | 1/2x+2/3(-3+3x)=-19/2 | | (3x^2+9x+8)/(x+2) | | 12x+2y=18 | | (3-5i)(2+i)= | | 3x-(12)=3 | | (x^2+10x+20)/x+5 | | 1/2(1+1/3y)+2/3y=-19/2 | | y+3=-3/4x-(-3/4)*1 | | 2x-1/5+2x=19 | | 0.003*x^3+0.02*y^2=sin(0.01x^2) | | ((2x-1)/5)+2x=19 | | 4x+16/x^2+4x | | Yi=16-0.5xi | | 27x-24(-0.25+1.125x)=6 | | 7x+21y=63 | | 8y=9x-2 | | 32x-4(8x+6)=24 | | 15(.2)=4+5x | | 12x+2x=16 | | (2x+3)(x)=629 | | 15(-0.8+3y)-20y=-7 | | 5x=15y-4 | | -2(10-5g)-4g=9+16g |

Equations solver categories